ANALISIS KEPUASAN MASYARAKAT DALAM LAYANAN PENDIDIKAN - Aryo Wibisono; Miftahol Arifin (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
The government as the control holder of a country has several programs in in thewelfare of the society,one of them is the program in the public service. This study aims todetermine the public satisfaction in education public services in Sumenep Regency. Theresearch method used is analysis tools of index of public satisfaction toward publicservice. In addition, this study can showed the characteristics of respondents and desiredpriorities of the public as users of education services and obtained the index of publicsatisfaction of schools in Sumenep Regency. The results showed that the majority of thepublic felt satisfied with the services of the school, because the school responded to anycomplaints from the guardians of the students. The public prioritizes the expertise of theteaching material and the quality of teachers needs to be improved. Index of publicsatisfaction of education services in Sumenep showed the "very good" level.